Sensor technology handbook. - Wilson, Jon S., ....- (Amsterdam : Elsevier, 2005)
Ch. 1 Sensor fundamentals Ch. 2 Application considerations Ch. 3 Measurement issues and criteria Ch. 4 Sensor signal conditioning Ch. 5 Acceleration, shock and vibration sensors Ch. 6 Biosensors Ch. 7 Chemical sensors Ch. 8 Capacitive and inductive displacement sensors Ch. 9 Electromagnetism in sensing Ch. 10 Flow and level sensors Ch. 11 Force, load and weight sensors Ch. 12 Humidity sensors Ch. 13 Machinery vibration monitoring sensors Ch. 14 Optical and radiation sensors Ch. 15 Position and motion sensors Ch. 16 Pressure sensors Ch. 17 Sensors for mechanical shock Ch. 18 Test and measurement microphones Ch. 19 Strain gages Ch. 20 Temperature sensors Ch. 21 Nanotechnology-enabled sensors Ch. 22 Wireless sensor networks: principles and applications App. A Lifetime cost of sensor ownership App. B Smart sensors and TEDS FAQ App. C Units and conversions App. D Physical constants App. E Dielectric constants App. F Index of refraction App. G Engineering material properties App. H Emissions resistivity App. I Physical properties of some typical liquids App. J Speed of sound in various bulk media App. K Batteries App. L Temperatures
Keywords: Sensoren